Association between sports type and overuse injuries of extremities in children and adolescents. a systematic review - Cheron, C.; Le Scanff, C.; Leboeuf-Yde, C. (Chiropractic & Manual Therapies, 2016)
Background: Sporting activities can cause injuries and overuse injuries of the extremities (OIE) in children have been shown to be more common than injuries caused by trauma. The lower extremity is more frequently affected than the upper extremity in OIE, but it is not known whether injury site and diagnosis vary in different sporting activities. Purpose: To identify any differences between sports in relation to diagnoses and anatomical areas most likely to be injured. Methods: A search was made in November 2014 and again in June 2016 in PubMed, SportDiscus, PsycInfo and Web of Sciences. Search terms were: « overuse injuries OR cumulative trauma disorders OR musculoskeletal injuries » AND « extremity OR limb » AND « physical activity OR sport OR risk factor OR predictors OR exercises » AND « child OR adolescent OR young adults ». Inclusion criteria were: 1) prospective, retrospective, or cross-sectional study design; 2) age=19 years; 3) the articles must clearly state if reported cases were classified as traumatic or overuse injuries; 4) reporting on OIE in relation to a particular sports type, and 5) sample size >50. A blinded systematic review was conducted. Results: In all, nine of the 736 identified articles were included, studying soccer, handball, orienteering, running, dance, and gymnastics. The incidence of OIE was given only in a few articles but at least the site and diagnosis of OIE were identifiable. The lower limb is more often affected than the upper in all sports covered, and, in general, the lower leg and knee are the two most often affected areas. However, in handball, the elbow was the second most often reported area, and in gymnastics injuries of the foot appeared to be more frequent than in the other sports. No differences in diagnoses were observed between sports types. Conclusion: Our work contributes new information, namely that the site of OIE in children and adolescents appears to vary only somewhat between different types of sports. Further well-designed surveillance studies are needed to improve knowledge that can help prevent injuries in children and adolescents participating in sports activities.